Strangers in death - Robb, J. D., 1950- (New York : Berkley Books, 2008)
The death of a prominent businessman in 2060 New York prompts Lieutenant Eve Dallas to seek assistance from her billionaire husband, an investigation that proves complicated when clues suggest that the killer had been known by the victim's family
Originally published: New York : G.P. Putnam's Sons, c2008
Keywords: Mystery fiction